2020
DOI: 10.1080/10942912.2020.1713152
|View full text |Cite
|
Sign up to set email alerts
|

Enzymolysis kinetics and structural-functional properties of high-intensity ultrasound-assisted alkali pretreatment ovalbumin

Abstract: This research investigated the enzymolysis kinetics of high-intensity ultrasound (HIU)-assisted alkali pretreatment Ovalbumin (OVA) through using Alcalase, and its structural and functional properties. The structural characteristics of OVA were performed with sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), surface hydrophobicity, Fourier Transform Infrared, and differential scanning calorimetry. SDS-PAGE analysis indicated that the pretreatment sample showed proportion of lower molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Gly is the predominant amino acid in collagen, contributing to intramolecular hydrogen bonding perpendicular to the helical axis, thus stabilizing its structure [38] . All tested samples contained significant amounts of hydrophobic amino acids, including Ala, Leu, Met, Phe, Pro, Thr, and Val, which have been reported in antioxidative peptides [11] , [24] . Previous studies have reported that the higher hydrophobic amino acids in proteins and their hydrolysates govern the higher antioxidative activities [24] , [31] .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Gly is the predominant amino acid in collagen, contributing to intramolecular hydrogen bonding perpendicular to the helical axis, thus stabilizing its structure [38] . All tested samples contained significant amounts of hydrophobic amino acids, including Ala, Leu, Met, Phe, Pro, Thr, and Val, which have been reported in antioxidative peptides [11] , [24] . Previous studies have reported that the higher hydrophobic amino acids in proteins and their hydrolysates govern the higher antioxidative activities [24] , [31] .…”
Section: Resultsmentioning
confidence: 85%
“…Based on the amino acid composition in the present study, the control had the highest hydrophobic amino acid content (9.76 %), followed by UP-20 (9.26 %) and US-30 (9.11 %), which was not in accordance with their antioxidative activities. The antioxidative properties of peptides are known to be greatly influenced not only by their amino acid composition or peptide size, but also by the molecular configuration that determines peptide folding behavior and exposure of hydrophobic patches on their surface [11] , [34] , [39] . The results indicated that the different amino acid compositions of CHs might govern changes in the secondary structure of peptides induced by UAP, which was more likely related to the variation in their antioxidative activity [40] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein can be hydrolyzed by protease under mild conditions in order to achieve the purpose of protein modification, without reducing the nutrition of food value, which can even increase the functionality of the protein (Liang et al, 2020). Liu et al found that protein side‐chain reaction in chemical modification can preserve or alter the electrostatic charge and enhance the functional properties of proteins (Liu, Hao, et al, 2020). Katekhong and Charoenrein (2017) studied the effect of SD temperature on the physical properties, solubility, and gelling properties of egg white protein powder and determined the relationship between the storage stability of the sample, temperature, and time, providing a basis for the production and storage of protein powder.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the methods for modifying OVA mainly include physical, chemical, and enzymatic methods, by changing the amino acid composition, sequence of ovalbumin, the size of the protein molecule, the number of hydrophobic groups, and the surface electrostatic charge etc. (An et al, 2014;Liu, Hao, et al, 2020).…”
mentioning
confidence: 99%